ANALISIS PENGARUH KUALITAS PRODUK DAN PERSEPSI HARGA TERHADAP KEPUASAN PELANGGAN LISTRIK PRABAYAR PT.PLN (PERSERO) RAYON BANGKO KABUPATEN MERANGIN - Isman (Jurnal Ekonomi Manajemen, 2020)
This study aims to see the alarms seen by simultaneous sound and the perception of the price of customer satisfaction of prepaid electricity PT. PLN (Persero) District Bangko Merangin Regency. The population in this study were 46,855 respondents and the sample was 100 respondents using the Slovin formula. The sampling technique is purposive sampling. Based on the results of multiple linear regression analysis, the equation Y = 10,164 + 0,264 X1 + 0,747 X2 + e. Test results of all variables have a positive and significant effect on customer satisfaction. Meanwhile, the results of the F test of all variables simultaneously have a significant effect on customer satisfaction for Prepaid Electricity PT PLN (Persero) Rayon Bangko Regency Merangin. The coefficient of determination (R2) of 0.711 indicates that product quality and price perception have a positive and significant effect of 71.1 percent on customer satisfaction for prepaid electricity PT. PLN (Persero) District Bangko Merangin Regency. And other factors not examined in this study had a positive and significant effect of 28.9 percent.